هۆكاروجێكه‌وته‌كانی ڕه‌زامه‌ندیی پیشه‌یی مامۆستایانی زانكۆ (توێژینەوەی هەڵێنجراو) - کریم, لقمان صاڵح; حسن, شاتوو فەرهاد (Sulaimani Journal for Humanities, 2023)
Job satisfaction is an important subject that has a considerable role in work environment. low job satisfaction or lack of job satisfaction will effect each of (psychology, work environment, job communication, management, production, development and progressing establishments) and in the presence of job satisfaction, the positive effects will appear on each of mentioned fields. Because of this, it is very important to take job satisfaction seriously in work environment. Special studies should be held in the different types of work. Furthermore, the researcher has run this theoretical research under the name of (reasons and segregations of job satisfaction through university instructors). Researcher has used sources, thoughts of thinkers and prior researches. In this research, the researcher has tried to show the content of the concept, the importance, and specifications. This research contains of two main sections and each of the sections held some parts. The first section contains of three parts. In the first part, mention each of (problem, importance, and objective) of the research. In second part, description of the concepts. In the third part, the previous researches have been talked about. The second section is explaining the concept of job satisfaction which contains of four parts. First part is the explanation of the job satisfaction concept in the view of experts. Second part is explaining the importance of job satisfaction and specifications. The third part is the reasons and effects of job satisfaction. The fourth part is the results, recommendations and suggestions. At the end, all the sources have shown. `